Pengaruh Pendidikan Kesehatan Explicit Instruction Terhadap Perubahan Perilaku Penanganan Cedera Di Komunitas Breakdance - Lucy Kartika Dewi; Erna Dwi Wahyuni; Deni Yasmara (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Background: Injury isa condition causes the body getting damage by physical pressure or chemical.The breakdance community members need to know the ability of the first injury handling. Objective: The purpose of this study is to analyze the influence of health education with explicit instruction method towards the injury handling behavior in Surabaya breakdance community.Methods: This study used quasy experimental design with pre-test and post-test in two groups. It comprised 13 treatment group and 13 control group respondents. This study used purposive sampling. The data were analyzed by Wilcoxon Signed Rank Test, Mann Whitney Test and Chi Square Test significance p<0,05. Results: The Wilcoxon Signed Rank Test result of the treatment group respondents showed knowledge (p = 0.001) and action (p = 0.001). The control group respondents showed the knowledge(p= 0.102) and action (p = 1,000). The Mann Whitney Test result between the treatment and control group were obtained knowledge(p = 0.000) and action (p = 0.000). For the Chi Square Testgot the attitude (p=0.047).Conclusion: This research shows the health education with explicit instruction method influences the breakdance community member’s behavior in injury handling. It suggests for further research to undertake the health education by using other methods.